Designing SQL server 2000 databases for .net enterprise servers - Bordwell, Darlene (Rockland, MA : Syngress, 2001)
The Microsoft .NET initiative is the future of e-commerce - making it possible for organisations to build a secure, reliable e-commerce infrastructure. This is the first book to outline the capabilities of SQL Server 2000, one of the key components of .NET. SQL Server 2000 introduces powerful new data mining functionality designed specifically to capture and process customer profiles and to predict future buying patterns on e-commerce sites. Designing SQL Server 2000 Databases for NET Enterprise Servers addresses the needs of IT professionals migrating from the popular SQL 7 databases to the new SQL 2000, as well as those who are starting from scratch. * Covers all key features of SQL Server 2000 including; XML support, enhanced data-mining capabilities and integration with Windows 2000 * While there are many books available on SQL 7 - this is the first to be announced for SQL 2000 * Free ongoing customer support and information upgrades.
Includes index.
Keywords: SQL server; SQL/DS.; Client/server computing; Database management; Database design; Web databases; Electronic books